Case of Donath-Landsteiner haemolytic anaemia in an adult female. (8th November 2018) - Bhatt, Ruchi; Calvo, Luis; Raju, Gagan; Podrumar, Alida
Abstract : Donath-Landsteiner haemolytic anaemia (DLHA), also known as paroxysmal cold haemoglobinuria, is a very rare and difficult condition to diagnose as well as treat. Here, we present a case of a 55-year-old Hispanic woman who presented with severe intravascular haemolytic anaemia in the setting of a viral illness 2 weeks prior to presentation. Direct antiglobulin testing revealed mixed results: positive for either complement, IgG or both on various occasions which led to a battery of tests including the Donath-Landsteiner antibody testing which turned out positive establishing the diagnosis of DLHA. She was initially treated unsuccessfully with supportive care in the form of packed red blood cell transfusions and steroids as well as rituximab for about 4 weeks but her condition improved on cyclophosphamide, and she is on the road to recovery after 10 weeks of hospital stay.